(untitled) (Economics and region, 2023)
The aim of this work is to develop the most optimal algorithm for calculating supplier ratings, which is an important element of supply chain management. The article analyzed existing methods for calculating a supplier’s rating and identified their shortcomings. An algorithm for calculating supplier ratings based on both expert data and statistical data has been described. The study highlights the key criteria that are relevant for evaluating suppliers, grouping them into those related to the general condition and capabilities of the supplier, those related to the reliability of the supplier’s business, and those related to operational risks. The proposed algorithm for evaluating supplier rating criteria involves collecting statistical data in the form of disincentive factors. The algorithm calculates the supplier rating by considering the ratio of the value of the disincentive factor that describes a particular supplier’s condition to the average market value of such a disincentive factor. The algorithm also takes into account changes in the values of supplier evaluation criteria over time. The study suggests comparing the results of the supplier rating with the classification of suppliers according to the ABC analysis method. Based on this comparison, the study proposes a business logic approach: if the supplier is promising based on the rating but does not fall into group A according to the ABC analysis, an action plan should be developed to improve cooperation with the supplier. If the supplier is unpromising based on the rating and falls into group A according to the ABC analysis, urgent measures should be taken to remove the supplier from the company’s partner list. Finally, if the supplier belongs to group A according to the ABC analysis and is promising according to the rating, a strategy should be developed for negotiating their price policy in relation to the company. The conclusion has been formulated that the algorithm proposed in the study for rating criteria evaluation will enable companies to make an effective choice of suppliers.